Metaphor Research and the Hebrew Bible - Lancaster, Mason D. (Currents in biblical research, 2021)
This article provides an overview of metaphor theories and research on their own terms, as well as their use in Hebrew Bible (HB) studies. Though metaphor studies in the HB have become increasingly popular, they often draw upon a limited or dated subset of metaphor scholarship. The first half of this article surveys a wide variety of metaphor scholarship from the humanities (philosophical, poetic, rhetorical) and the sciences (e.g., conceptual metaphor theory), beginning with Aristotle but focusing on more recent developments. The second half overviews studies of metaphor in the HB since 1980, surveying works focused on theory and method; works focused on specific biblical books or metaphor domains; and finally noting current trends and suggesting areas for future research.